Modelling of Three-Dimensional Nanographene - Mathioudakis, Christos; Kelires, Pantelis C. (My University, 2016)
Monte Carlo simulations and tight-binding calculations shed light on the properties of three-dimensional nanographene, a material composed of interlinked, covalently-bonded nanoplatelet graphene units. By constructing realistic model networks of nanographene, we study its structure, mechanical stability, and optoelectronic properties. We find that the material is nanoporous with high specific surface area, in agreement with experimental reports. Its structure is characterized by randomly oriented and curved nanoplatelet units which retain a high degree of graphene order. The material exhibits good mechanical stability with a formation energy of only ∼0.3 eV/atom compared to two-dimensional graphene. It has high electrical conductivity and optical absorption, with values approaching those of graphene.
Keywords: 3D graphene; Absorption; Conductivity; Electronic structure; Monte Carlo simulations; Rigidity; Structure; Tight-binding calculations